Exceptional Performance of Hierarchical Ni–Fe (hydr)oxide@NiCu Electrocatalysts for Water Splitting. Issue 8 (27th December 2018) - Zhou, Yongfang; Wang, Zixu; Pan, Ziyan; Liu, Le; Xi, Jingyu; Luo, Xuanli; Shen, Yi
Abstract: Developing low‐cost bifunctional electrocatalysts with superior activity for both the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is of great importance for the widespread application of the water splitting technique. In this work, using earth‐abundant transition metals (i.e., nickel, iron, and copper), 3D hierarchical nanoarchitectures, consisting of ultrathin Ni–Fe layered‐double‐hydroxide (Ni–Fe LDH) nanosheets or porous Ni–Fe oxides (NiFeOx ) assembled to a metallic NiCu alloy, are delicately constructed. In alkaline solution, the as‐prepared Ni–Fe LDH@NiCu possesses outstanding OER activity, achieving a current density of 10 mA cm −2 at an overpotential of 218 mV, which is smaller than that of RuO2 catalyst (249 mV). In contrast, the resulting NiFeOx @NiCu exhibits better HER activity, yielding a current density of 10 mA cm −2 at an overpotential of 66 mV, which is slightly higher than that of Pt catalyst (53 mV) but superior to all other transition metal (hydr)oxide‐based electrocatalysts. The remarkable activity of the Ni–Fe LDH@NiCu and NiFeOx @NiCu is further demonstrated by a 1.5 V solar‐panel‐powered electrolyzer, resulting in current densities of 10 and 50 mA cm −2 at overpotentials of 293 and 506 mV, respectively. Such performance renders the as‐prepared materials as the best bifunctional electrocatalysts so far. Abstract : 3D core–shelled nanoarchitectures are synthesized, consisting of NiFe‐layered‐double‐hydroxide nanosheets/porous NiFe oxides assembled to a metallic NiCu alloy, as bifunctional electrocatalysts for overall water splitting. The superior performance is demonstrated by a 1.5 V solar‐panel‐powered electrolyzer, yielding current densities of 10 and 50 mA cm −2 at overpotentials of 293 and 506 eV, respectively.